The Effect Of Aloe Vera Compress On Reducing Body Temperature In Children With Fever After Pentavalent Dpt Immunization - Setiasih, Sri; Setiasih, Sito; Yuliani, Diki Retno (JKM (Jurnal Kebidanan Malahayati), 2025)
Background: The incidence of Adverse Events Following Immunization (KIPI) at Kalibagor Public Health Center from January to October 2022 reached 10 cases, distributed across eight villages in Kalibagor Subdistrict. All cases were managed properly without resulting in permanent physical disability. The most common AEFI was fever in children following DPT-Pentavalent immunization. Efforts to reduce fever after DPT-Pentavalent immunization include pharmacological and non-pharmacological therapies. One of the non-pharmacological interventions is compress therapy, which can be independently applied by nurses or parents. Compresses do not necessarily require warm water; an alternative method is aloe vera compress. Aloe vera compress works through conduction, as the water content in aloe vera gel absorbs body heat, transferring heat from the child’s body into the aloe vera. Conduction occurs between the aloe vera and surrounding tissues, including blood vessels, thereby lowering body temperature. The cooled blood then circulates throughout the body, continuing the conduction process until the body temperature decreases.Objective: To analyze the effect of aloe vera compresses on reducing body temperature in children experiencing fever after DPT-Pentavalent immunization, to describe body temperature before and after aloe vera compress application, and to examine the significance of the intervention on temperature reduction.Methods: This study employed a quantitative approach with a quasi-experimental design using a one-group pretest–posttest method. Body temperature was measured twice, before and after aloe vera compress application. The study population consisted of all infants aged 2–4 months in January 2023 who received DPT-Pentavalent immunization in Kaliori Village, Kalibagor Public Health Center, Banyumas Regency. In April 2023, there were 32 infants aged 2–4 months, all of whom were included as the research sample. Research instruments included a digital thermometer, informed consent forms, observation sheets, and standard operating procedures (SOPs) for aloe vera compress application.Results: Prior to aloe vera compress application, all infants developed fever (temperature >37.5°C) after DPT-Pentavalent immunization. Following the intervention, most infants (20 infants; 62.5%) returned to normal body temperature, while 12 infants (37.5%) still had fever. The Kolmogorov–Smirnov normality test showed a significance value of 0.000, indicating non-normal data distribution (p < 0.05). Therefore, the Wilcoxon signed-rank test was applied, yielding a p-value of 0.0001 (p < 0.005). This result indicates a significant difference in body temperature before and after aloe vera compress application.Conclusion: Aloe vera compress application significantly reduces body temperature in children with fever following DPT-Pentavalent immunization.